Indicadores das oscilações da linha de costa nas praias de Aracaju-SE entre os anos 2013-2018 e sua relação com, as derivações antropogênicas - Silva, Daiany Santos (2019)
Changes in coastal zones cause constant morphodynamic adjustments of the shoreline resulting from natural and human processes. This thesis emphasizes the beaches of the municipality of Aracaju, located on the central coast of the State of Sergipe - Brazil, which have approximately 24 km of shoreline and represent the most odd part of the coast of Sergipe as the potion is the most urbanized and with consequent impacts resulting from human actions, but still possess well preserved stretches compared to other capitals of the Brazilian Northeast. Therefore, the objective of this study is to evaluate the time space evolution (2013-2018) of the Aracaju shoreline, addressing the anthropogenic derivations occurred in the area. The research methodology was qualified as a quantitative and qualitative type, since it contains information about the physical and anthropic environment, and has an exploratory character that understands the causes and effects of this connection in the beaches. This approach has as fundamental principle, an integrated and interdisciplinary vision of the problematic in question. The research was carried out in 5 main steps: bibliographical survey, fieldwork, elaboration and analysis of database, diagnosis of evolution with elaboration of cartographic products and evaluation of the correlations of products with the anthropogenic derivations of the coast. The mapping was carried out with the help of GPS TRIMBLE R6 technology, which enabled the work with data along with high resolution and precision, the delimitation of the shoreline in the field was given through geoindicators, being the principals, the beach erosion scarp and the line of hightide. The coast line was assigned with three classes according to the processes indicated in the excerpts, being them: progradation, dynamic balance and erosion. Therefore, it was diagnosed that 46% of the beaches in the Aracaju coast are in a progradational process, 46% in equilibrium and 8% in erosion. It was evidenced that the most significant processes of erosion and progradation are found to the north and are related to the mouth of the Sergipe river. With advancement of the shoreline of up to 227 m and retreat of up to 20 m in 5 years. In 2018 only 15% of the beaches were mapped through the geoindicator beach erosion scarp, compared to 54% in 2013. This change in beach morphology reflects its overall trend, which is balanced and progradational. In addition, the study shows that the shoreline oscillations are also directly influenced by anthropogenic derivations, especially those related to urban growth and coastal protection works implemented. The data generated in line; with the latest research developed in the area, make clear the scenario of instability and consequent socio-environmental risks, strengthening the importance of continuous monitoring of the shoreline for the effective management of Aracaju’s coast.